TASK-BASED ASSESSMENT OF PRAGMATIC COMPETENCE: A MOROCCAN EFL HIGH SCHOOL PERSPECTIVE - Bouknify , Mohammed (International Online Journal of Education and Teaching, 2025)
This study investigates Moroccan high school learners’ pragmatic competence in English as a Foreign Language (EFL) through two diagnostic tools: the Written Discourse Completion Test (WDCT) and the Multiple-Choice Discourse Completion Test (MDCT). Pragmatic competence, a critical dimension of communicative language ability, remains underrepresented in EFL assessment frameworks, particularly in North African contexts. Drawing on data from 108 learners, the research evaluates students’ ability to perform various speech acts appropriately in context-sensitive scenarios. Results show significant gaps in learners’ pragmatic awareness and performance, particularly in managing politeness, indirectness, and socio-cultural appropriateness. These findings underscore the need to integrate explicit pragmatics instruction and assessment into Moroccan EFL curricula. This article contributes to the growing body of empirical studies on interlanguage pragmatics and calls for a reconceptualization of language assessment practices in EFL classrooms. Keywords: Pragmatic competence, EFL, Morocco, WDCT, MDCT, speech acts, language assessment, interlanguage pragmatics